Ofertar-me: o batuque como propulsor do estado performático - Lara, Marcos Vinicius Caye (2015)
This paper aproaches a research on performance art. It is lectured here the mechanisms and keys that allow the performer to fully offer and deliver oneself to the other performer. This research gatter elements within the Batuque culture that enabled the performer to face the leap into the abyss that is to perform, which is, that allow to throw oneself on the here and now on in front of other. How to face this unknown person? Or, especially, how to conect with the unknown, with the other? On this thesis is presented the poetic and the keys that the author used for something to happen with him, to propose oneself experiences in art. These "keys" that the performer found open doors, shortcuts, to enter the state of performance and thus contact with the public. These keys found in the drumming of the rite became, in its majority, part of the poetic, which are constituent elements of performance, making it also the trigger element of the experience with and before other. Five Performances were created from this research, namely: How to explain the sacrifice of a chicken , berried in wealth the body ends up to sufocate. Sit down! Listen , Holly Spirit of 7 Crossroad , From the same mud you came e for the same mud shall return .